SURGICAL ANATOMY OF THE VEIN OF LABBE AND VEINS DRAINING THE TEMPOROBASAL SURFACE OF THE TEMPORAL LOBE AND THEIR ROLE IN LATERAL APPROACHES - R. N. Lyunkova; P. A. Lopanchuk; A. V. Gushchin; E. A. Mishurinskaya; V. A. Bendosenko; V. V. Krylov (Вестник медицинского института «Реавиз»: Реабилитация, врач и здоровье, 2020)
Lateral approaches (standard subtemporal and a number of lateral and combination basal approaches) ensure access to the clivus, petroclival area, cerebellopontine angle (CPA), and lateral and posterolateral portions of the cavernous sinus. The complexity of surgeries performed via lateral approaches is attributed to the topography of the skull base, location of the sites where the vein of Labbe unites with large veins of the mediobasal surface of the brain, draining the lateral and basal surface of the temporal lobe into major venous collectors. The vein of Labbe and veins draining the temporal lobe are located in the area of operational axis and significantly limit or hinder active traction of the brain. Therefore, preservation of these veins is crucial in surgeries via lateral approaches. The location of sites where the veins draining the temporal lobe and lower anastomotic vein of Labbe unite with sinuses may vary. Therefore, the study of microsurgical anatomy of the veins draining the temporal lobe and vein of Labbe is an important aspect of skull base surgery.